Experimental investigation on effect of corrosion on resonant frequency of concrete cylinders - Devi, A. Kanchana; Sivasubramanian, K.; Ramajaneyulu, K. (Journal of Structural Engineering, 2025)
Corrosion of steel in reinforced concrete structures produces damage in the form of delamination and cracking followed by spalling of cover concrete, leading to reduction in load carrying capacity, large deflections, etc. In general, the above phenomenon results in the loss of integrity of the component/member. The loss of integrity is reflected as change in the resonant frequency of the system. In the present study, an attempt is made to study the effect of different levels of corrosion on the resonant frequency of concrete cylinders. The resonant frequencies of the cylinders are evaluated by processing the acceleration data acquired during testing of cylinders using resonance tester. The resonant frequencies of the specimens with and without the effects of corrosion are evaluated. The changes in resonant frequencies of concrete cylinders due to different levels of corrosion are reported in the paper. The effects of corrosion on frequency response of the system are also discussed.